Are blood pressure and cardiovascular stress greater in isometric or in dynamic resistance exercise? - Kounoupis, A.; Papadopoulos, S.; Galanis, N.; Dipla, K.; Zafeiridis, A. (Sports, 2020)
Medical and sports medicine associations are reluctant to endorse isometric exercise to the same extent as dynamic resistance exercise (RE). The major concern is the fear of greater increases in blood pressure (BP) that might be associated with isometric exercise. This review comprehensively presents all human studies that directly compared the magnitude of hemodynamic responses between isometric and dynamic RE. We also discuss possible mechanisms controlling BP-response and cardiovascular adjustments during both types of RE. The most prominent finding was that isometric and dynamic RE using small-muscle mass evoke equal increases in BP; however, the circulatory adjustments contributing to this response are different in dynamic and isometric RE. In contrast, studies using large-muscle mass report inconsistent results for the magnitude of BP-response between the two types of RE. Thus, when the same muscles and workloads are used, the increase in BP during isometric and dynamic RE is more comparable to what is commonly believed. However, it should be noted that only a few studies equalized the workload in two types of RE, most used small sample sizes, and all studies employed healthy participants. More studies are needed to compare the cardiovascular risks associated with isometric and dynamic RE, especially in individuals with chronic disease.